MANAJEMEN RISIKO TRANSAKSI DAN PENCAIRAN TRAVELLER’S CHEQUE GUNA PENCEGAHAN TINDAK PIDANA DI BIDANG PERBANKAN - Hassanain Haykal (Fakultas Hukum Universitas Pasundan, 2016)
Bank in carrying out all its activities tied to various banking regulations, including the principles and fundamental principles in banking law. In conducting its operations, the bank will continue to deal with the risk that risk management systems and the application of the precautionary principle should be applied consistently. At now, the development of banking products and services is growing rapidly. In payment traffic, the currently known range of payment instrument issued by a bank, including the Travel Cheque. Flexibility of Travel Checks lead easily abused and used as a means of conducting illegal transactions. Travel Checks are commonly abused as a means of conducting a criminal act such as bribery, graft acceptance, and as a means of laundering money. Keywords : Risk Management, Traveller’s Cheque, Crime in Banking.